2018
DOI: 10.1002/mrd.22987
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of camel whey protein against scrotal heat‐mediated damage and infertility in the mouse testis through YAP/Nrf2 and PPAR‐gamma signaling pathways

Abstract: Elevation of scrotal temperature is one of the most important causes of impaired spermatogenesis and male infertility, but the exact mechanism remains controversial. The present study investigated the impact of camel whey protein (CWP) on the mechanisms of heat stress (HS)-mediated testicular damage in male mice. Exposure to HS was associated with significant increase in the testicular tissues' oxidative stress. Mechanistically, exposure to HS resulted in upregulation of P53 and Nrf2 expressions; downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…cells increases in the mouse testis following chronic heat stress (Badr, Abdel-Tawab, Ramadan, Ahmed, & Mahmoud, 2018). To this point, no study has evaluated the role of Hippo signaling in mammalian testicular germ cells, but two studies have suggested a potential role for this pathway in germ cell development.…”
mentioning
confidence: 99%
“…cells increases in the mouse testis following chronic heat stress (Badr, Abdel-Tawab, Ramadan, Ahmed, & Mahmoud, 2018). To this point, no study has evaluated the role of Hippo signaling in mammalian testicular germ cells, but two studies have suggested a potential role for this pathway in germ cell development.…”
mentioning
confidence: 99%
“…Mohamed et al [ 20 ] reported that prophylactic CM administration improved spermatogenesis activity with the right spermatozoa percentage. Badr et al [ 60 ] reported the effects of camel whey protein in protecting mice’s testes from scrotal heat-induced damage and infertility. Moreover, Faraji et al [ 61 ] reported that the administration of silymarin to the cadmium chloride rats prevented changes in the testicular histological characteristics and testosterone levels in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, YAP is involved in the heat stress mediated testicular damage. 35 In addition, the Hippo signalling pathway in skeletal muscle is involved in the regulation of exercise adaptation. 28 However, both the exercise (physiological limitation) and heat stress (environmental factor) are the most importantly predisposing factors for EHS.…”
Section: Discussionmentioning
confidence: 99%
“…The strong and rapid YAP activation in cancer cells was induced by heat stress for the expression of heat shock proteins, 26 which is also suggested by our analysis. Additionally, YAP is involved in the heat stress mediated testicular damage 35 . In addition, the Hippo signalling pathway in skeletal muscle is involved in the regulation of exercise adaptation 28 .…”
Section: Discussionmentioning
confidence: 99%